Penerapan Sosialisasi Pencegahan Kenakalan Remaja dan Pengenalan Kampus Uin Sgd Bandung Di Desa Ciasem Girang - Kurniasari, Dewi; Siddiq, Fakhri; Hasabi, M Ikbaarshaff; Faujiah, Yulianti (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Education is one of the important pillars in the progress of a country, objectively education is a form of one of the qualities of a citizen, the progress index of a country can be seen from where its education takes place, if education in a country is good then the index of a nation is also good. also as good as it gets. Teenagers are an asset for the future of a nation. But nowadays a lot is happening to teenagers, such as drugs and motorcycle gangs. This is a familiar problem. Juvenile delinquency includes all behavior that deviates from criminal law norms committed by adolescents. Lots of internal and external factors that cause juvenile delinquency that need attention. To overcome this, guidance from parents and also a good environment can be a determinant for the development of these adolescents.